The impact of the criminal law (sexual offences and related matters) amendment ACT 32 OF 2007 on the offence of rape and sentencing thereof - Curlewis, Llewelyn Gray (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria, 2019.